The Conversion of the Nations in Revelation. By Allan J. McNicol - Downing, Jonathan (The journal of theological studies, 2012)
This monograph aims to solve a key problem in Revelation’s treatment of ‘the nations’: how can the author welcome the nations into the New Jerusalem (21:24–6, 22:2) after he presents their hostility to the Lamb’s followers and their apparent destruction earlier in the text (19:15)? McNicol’s solution to this problem balances a careful analysis of material in the Apocalypse concerning ‘the nations’ while trying to evoke John’s ‘pastoral’ concerns vis-à-vis the churches he is addressing., McNicol’s fundamental argument is that there is a coherency in John’s discussion of the nations’ destiny which is revealed through a consideration of his overall eschatological plan. His argument begins with a critique of rival explanations of this theme in Revelation by Richard Bauckham and J. P. M. Sweet.